Prevalence and Risk Factor of Hepatitis B among Pregnant Women in Prof. Dr. W. Z. Johannes Hospital Kupang, East Nusa Tenggara, Indonesia - Tangkelangi, Marni; Wuan, Adrianus Ola; Rogaleli, Yuanita Clara Luhi (Poltekkes Kemenkes Palu, 2023)
Introduction: Hepatitis B (HB) during pregnancy was a treating condition for both mother and fetus. Prevalence of Hepatitis B in Indonesia was 0,39 and Kupang City was 0,37 based on Riskesdas in 2018. Purpose: This study aims to measure the prevalence of hepatitis and its risk factors among pregnant women in Prof. Dr. W. Z. Johannes Hospital Kupang. Methods: This study was a descriptive qualitative research using cross sectional design, population was all pregnant women underwent HBsAg Rapid Test excluded HIV co-infection, the sample of this study was 345 pregnant women who visited the hospital during 2021 using constitutive sampling technique, prevalence of hepatitis was calculated and data obtained was analysed using chi-square and fisher exact test for the risk factor. Results: Prevalence of Hepatitis B were 19.7% (66 of 345). Risk factor of hepatitis B on this study was >1 sexual partner (p= 0,000, OR= 53,26), while age (p = 0,597), gestational age (p = 0,597), and parity (p = 0,329) were not the risk factors in this study. Conclusion: Prevalence of Hepatitis B among pregnant women was high, having >1 sexual partner was risk factor of pregnant women in Prof. Dr. W. Z. Johannes Hospital Kupang. It is recommended to encourage early detection and Hepatitis B vaccine on pregnant women to provide specific protection.